Innovation Design of Fertilizing Mechanism of Seeder Based on TRIZ Theory. Issue 17 (2018) - Yang, Liu; Yi, Shujuan; Mao, Xin; Tao, Guixiang
Abstract: In order to improve the mechanical performance and automation of the planter's fertilization device, this article uses the TRIZ theory for innovative design and guidance. It uses two screens, function analysis and two TRIZ tools to complete the design of the model, structure model and function model. Analyze many contradictory issues such as technical contradiction analysis and material field analysis to solve many problems. Finally, through the rational design of the electronically controlled part and the mechanical device structure, nitrogen, phosphorus, and potassium are automatically mixed and fertilized. It improves the utilization of nitrogen in China and avoids the waste of fertilizer, has high control precision, high reliability, saves costs, increases productivity, and achieves precision agriculture. Lay a good foundation for the realization of the modernization of agriculture.